Species inventory of aquatic macrophytes in the last undammed stretch of the Upper Paraná River, Brazil - Souza,Douglas Costa (2017)
Abstract The last undammed stretch of the Upper Paraná River in the Brazilian territory is, to date, not completely inventoried, which rises concerns given the rapid rates of species extinctions. Aim Here, we provide an inventory of macrophyte taxa recorded in the last undammed 230 km stretch of the Upper Paraná River. Methods We inventoried macrophyte taxa in 27 sampling stations including lakes, the main channel of the river, and the tributary confluences in November 2013 and in May and November 2014. Macrophyte were sampled in littoral zones. We explored taxonomic and life form aspects of the recorded species. We used species accumulation curves and ordination techniques to summarize the variation in richness and composition of macrophyte species. Results We recorded 71 macrophyte taxa in 35 families. Most species were emergent, amphibian, free-floating, and rooted submerged. At the main channel of the Upper Paraná River, Eichhornia azurea, E. crassipes, and Paspalum repens represented the most frequent species. The most frequent species in the tributary confluences were Ludwigia sp., E. azurea, and Polygonum ferrugineum, while in lakes, Ludwigia sp., Oxycaryum cubense, and E. azurea were the most representative taxa. In regard to macrophyte composition, the invasive Hydrilla verticillata mostly influenced sites in the Upper Paraná River, in the ordination space, while floodplain lakes were mostly characterized by the presence of species such as Scleria melaleuca, Panicum maximum, and Thelypteris sp., among others. Conclusions Our study indicates that the last undammed stretch of the Upper Paraná River contains a large number of macrophyte species, suggesting that this stretch is an important area for the conservation of macrophyte species. In addition, the occurrence of invasive species (e.g., Hydrilla verticillata) within the investigated stretch deserves attention in terms of potential impacts for which management action may be necessary.